Penanggulangan Tindak Pidana Korupsi Melalui Perspektif Pancasila - Nusantara P, Bayu; Melati, Dwi Putri; Silalahi, Wahrul Fauzi (JUSTICIA SAINS - Jurnal Ilmu Hukum, 2023)
The rise of criminal acts of corruption in Indonesia is contrary to the values of Pancasila as the life goal of the Indonesian nation, the problem in this research is how to deal with criminal acts through the perspective of Pancasila, this research method uses normative juridical methods, Pancasila has a very important role in upholding the rule of law, is philosophy, the basis of the state and open ideology. Pancasila is a source of enlightenment, a source of inspiration and as a basis for solving the problems faced by the Indonesian people in dealing with all types of violations and crimes in this case corruption.